Structure Analysis of Warren Truss Bridge Using 3D CAD Software - Satria, Adam; Adinda Rahmah Shalihah; Fadhil Fadhlurrohman Nurhadi; Ridho Hans Gurning; Sanurya Putri Purbaning (LPPM Politeknik Aceh Selatan, 2025)
The Warren truss consists of longitudinal members joined only by angled cross-members, forming alternately inverted equilateral triangle-shaped spaces along its length, ensuring that no individual strut, beam, or tie subjected to bending or torsion straining forces, but only to tension or compression. Tension and compression resulting from the reaction force from the load received. Every bridge has a load limit that can be received. These limits can be seen from the bridge safety factor. The purpose of the analysis of safety factor that occurs on a Warren truss bridge, i.e. to know the load limit that can be received for a bridge structure design, Warren truss types. On the bridge with a length of 57.38 m, 9.25 m wide bridge, with a thickness of 27.5 m of concrete, and asphalt thickness of 4.5 m, will be given a load containing 28 Toyota avanza 4 adults with 75 kg per person, which to determine load limits and safety factors of this bridge design. Before the static analysis, safety of factor and stress calculations performed with the determination of area of road A = 530.765 m2, the determination of the height of asphalt t = 0.045 m, and the determination of the height of concrete t = 0.275 m, this calculation aims to facilitate the determination of volume of asphalt and volume of concrete, and the results of maximum load obtained from the determination of volume, and the determination of gravitation to gain maximum load. From maximum load, it can be determined of reaction force that to be used for analysis. Stress analysis and safety factors analysis were performed using solidworks software.